How to Develop a Tripusat-Based Christian Character Education Curriculum at SMP Negeri 4 Manado - Ester Yuniati; Benny B. Binilang; Olivia Cherly Wuwung (International Journal of Education, Information Technology, and Others, 2023)
This development research aims to develop a product in the form of a Christian Character Education Curriculum based on Tripusat Pendidikan which in its implementation is integrated into PAK and Ethics subjects to improve the character of students at SMP Negeri 4 Manado. The curriculum was developed using Borg and Gall's research and development steps by modifying and combining the Grass Roots and Hilda Taba curriculum development models. The results of this research and development can be concluded that the Christian character education curriculum based on Tripusat Pendidikan developed is very good and worthy of use. There is an increase in religious character, honest character, disciplinary character, and reading character for students who in PAK and Ethics learning use this curriculum.